ΟΘΩΜΑΝΙΚΕΣ ΑΝΤΙΛΗΨΕΙΣ ΠΕΡΙ ΕΓΚΛΗΜΑΤΟΣ ΚΑΙ ΤΙΜΩΡΙΑΣ - ΑΝΑΣΤΑΣΟΠΟΥΛΟΣ ΑΝΤΩΝΗΣ; ΓΚΑΡΑ ΕΛΕΝΗ (Μνήμων, 1999)
Antonis Anastasopoulos - Eleni Gara, Ottoman perceptions of crime andpunishment The present essay deals with aspects of Ottoman justice and consists offour parts. Part I (Law transgression and court) discusses the prerequisitesfor a case to come up for hearing at the Ottoman sheriat court. Aseventeenth-century litigation from the town of Veria (Karaferye) servesas a model in order to define criminal behaviour and to demonstratehow private differences acquire both a public and legal meaning whenbrought to court. Part II (Proving an accusation) is focused on the issuesof evidence and testimony as a vital part of the legal procedure, usingas example an eighteenth-century litigation from Istanbul. Part III(Sentence and settlement) deals with the issues of the sentences that the kadi passed, and of out-of-court settlements as an alternative legalinstitution, which was recognized and respected by the Ottoman judges.Part IV (Authority abuse as a crime) treats justice as protection of thereaya from the abuses of the askeri in the context of the official stateideology. Stress is put on the use of formulas in documents. Those formeda code that allowed both the subjects of the empire and its authoritiesto enter a variety of illegal acts under the easily recognizable headlineof «oppression» and to treat them accordingly.The basic idea that permeates the article is that Ottoman justicewas dispensed on the basis of fixed principles and procedures, and thatit is incorrect to treat the kadi as an arbitrary judge who adjudicatedat whim. These principles and procedures, though originating to a greatextent in the Islamic holy law, can be considered as Ottoman in thesense that they were redefined and given a new meaning within theEmpire’s legal framework. Lastly, throughout the article special emphasisis put on the use of records of litigations, especially kadi sicilleriand ahkâm defterleri, as a means of reconstructing the Ottoman systemof dispensation of justice and of establishing the degree of its conformityto and deviation from the Islamic sheriat.